The Effect of Self-Compassion and Gratitude on University Students Life Satisfaction: Social Support as the Mediator - Cita Aruni, Vradita; Mugiarso, Heru; Sugiyo, Sugiyo (Jurnal Bimbingan Konseling, 2023)
University students often face various both academic and non-academic demands, expectations in society and many other life demands. These can surely raise various problems, anxiety, stress, decrease in concentration, achievement, motivation and even depression which will affect their life satisfaction and happiness. Even though life satisfaction is the significant part of psychological well-being, it can influence mental health conditions. Regarding this background, the aim of this study was to examine the effect of self-compassion, gratitude and social support on life satisfaction, and to examine the role of social support as the mediator variable in the effect of self-compassion and gratitude on life satisfaction. It used a quantitative non-experiment ex post facto design. Based on the Structural Equation Model (SEM) analysis of the structural model of self-compassion on life satisfaction through social support and the structural model of gratitude on life satisfaction through social support, the findings of this study have proved that the test of the direct influence of self-compassion, gratitude and social support on life satisfaction resulted positive and significant result, while social support was able to mediate the effect of gratitude on life satisfaction positively and significantly, but unable to mediate the effect of self-compassion on life satisfaction significantly.